Technical Requirements for Clinical Exercise Physiologists as Qualified Health Professionals. (March 2023) - Overstreet, Brittany; Ward-Ritacco, Christie; Neric, Francis; Brawner, Clinton A.; Thompson, Benjamin; Hargens, Trent; Thompson, Walt
Abstract : Despite meeting the required technical standards, clinical exercise physiologists (CEPs) have yet to be identified as qualified health professionals (QHPs). Lack of QHP status for CEPs has resulted in limited coverage of services by the Centers for Medicare & Medicaid Services (CMS), leaving CEPs ineligible to be reimbursed for many of the services they provide. Being acknowledged as a QHP would allow CEPs to better contribute to interprofessional health care teams and potentially become eligible for reimbursement for services provided by CMS and other insurance companies. Apply It!: Readers will be able to advocate for the field of clinical exercise physiology with an enhanced understanding of the current state of the profession. Readers will have a platform to have discussions with other allied health professionals to increase awareness of the role of a clinical exercise physiologist in a health care setting.